2020
DOI: 10.1371/journal.pone.0227521
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sport expertise and shot results on basketball players’ action anticipation

Abstract: The purpose of the present cross-sectional study was to clarify the effects of sport expertise and shot results on the action anticipation of basketball players. Eighty-eight male subjects participated in this study, namely, 30 collegiate basketball players, 28 recreational basketball players and 30 non-athletes. Each participant performed a shot anticipation task in which he watched the shooting phase, rising phase, high point and falling phase of a free throw and predicted the fate of the ball. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Using this framework, it has been established that elite athletes possess superior perceptual-cognitive skills when compared to intermediate and non-elite performers [ 21 , 22 , 23 ]. The application of this approach in a basketball-specific context revealed expertise effects in anticipation [ 24 , 25 , 26 , 27 ], pattern recall [ 28 , 29 , 30 , 31 , 32 ], and visual search strategies [ 33 , 34 ]. Advantages are also reported when focusing on decision-making skills: Spittle et al [ 35 ] found that participants who currently played basketball or played at a higher level of competition made more correct decisions in a video-based test than those currently not playing or doing so on a lower level of competition.…”
Section: Introductionmentioning
confidence: 99%
“…Using this framework, it has been established that elite athletes possess superior perceptual-cognitive skills when compared to intermediate and non-elite performers [ 21 , 22 , 23 ]. The application of this approach in a basketball-specific context revealed expertise effects in anticipation [ 24 , 25 , 26 , 27 ], pattern recall [ 28 , 29 , 30 , 31 , 32 ], and visual search strategies [ 33 , 34 ]. Advantages are also reported when focusing on decision-making skills: Spittle et al [ 35 ] found that participants who currently played basketball or played at a higher level of competition made more correct decisions in a video-based test than those currently not playing or doing so on a lower level of competition.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by several studies, expert basketball players demonstrated better anticipation than novices [2][3][4], but the advantage was affected by the shot results [5][6][7]. Interestingly, experts could not predict better in all basketball shots.…”
Section: Introductionmentioning
confidence: 80%
“…The experts' judgement bias has been interpreted as the effect of "regulatory fit" [6]. The theory of regulatory focus presents two types of individual focus, namely promotion focus and prevention focus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Forward model computations contribute to learning (Jordan & Rumelhart, 1992), and extended experience in a motor task correlates with distinct signs of predictive error processing on the neurophysiological level (Lutz et al, 2013; Beaulieu et al, 2014; Maurer et al 2015; Joch et al, 2017; Maurer et al, 2021). Furthermore, it has been shown that motor experts (sports athletes) can anticipate the outcomes of other players’ actions with relatively little information about action parameters, and that this ability rises with skill level (Abreu et al, 2012; Aglioti et al, 2008; Li & Feng, 2020; Tomeo et al, 2013). In these studies, temporal occlusion paradigms were used, where participants with varying expertise levels watched videos of motor actions and had to predict the outcomes of the actions shown at different points in time.…”
Section: Discussionmentioning
confidence: 99%
“…The conscious accessibility of sensorimotor prediction with respect to action outcomes has been investigated in athletes involved in different sports. The focus of most studies has been on anticipatory estimates of other players’ actions, based purely on visual information, for example in basketball shooting (e.g., Abreu et al, 2012; e.g., Aglioti et al, 2008; Li & Feng, 2020; Özkan et al, 2019), volleyball smashes (e.g., Cañal-Bruland et al, 2011; Wright et al, 1990), soccer penalty kicks (Tomeo et al, 2013), or other game situations (for a review see Abreu et al, 2017). Since predictions in these studies were exclusively based on observations of motor actions, available sensorimotor information was incomplete, and visual information differed compared to when actions were executed.…”
Section: Introductionmentioning
confidence: 99%